Implementasi Pembayaran Royalti dalam Perjanjian Lisensi pada Penerbitan Buku - Tri Aktariyani (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2016)
The results showed that the system of royalties on book publishing has fourelements, namely the elements of the subject between the author as creator and publisheras the copyright holder, elements of the agreement that the payment of royalties onpublishing a book based on the agreements set forth in the agreement in the form of alicense agreement. object elements are exploiting the economic rights over creative workssuch as books, element in the system of royalty payments of book publishing is doneaccording to the agreement. Supervision of the number of books published, printed andsold can not be much that can be done because the mechanism of publishing authors inthe book marketing is extremely complicated, in this cooperation kepercayaanlahfoundation. The process of transfer of rights to the publication of the manuscript done bythe author to different publishers to do that is the end of the book publishingagreements, tort, and begins with the selection of the type of agreement on transfer of acreation which Exclusive License Agreement, the Non-Exclusive License Agreementand the surrender agreement.